Looking east: The European Union's new FTA negotiations in Asia - Razeen Sally (European Centre for International Political Economy (ECIPE), 2007)
In late 2006, Peter Mandelson, the EU trade commissioner, announced a new EU policy on free trade agreements (FTAs). This is contained in the European Commission's Global Europe Communication. The core of this new chapter in EU trade policy is planned FTAs with three Asian partners, India, ASEAN and South Korea. The Commission secured a mandate for new negotiations from the EU Council in April 2007. Negotiations have already started. The EU has thus joined the bandwagon of FTAs in Asia. It is not of course new to FTAs. Indeed, the EU has more preferential trade agreements (PTAs) on the books than any other leading power. But it did put new FTAs in deep-freeze from the late 1990s, giving priority instead to the WTO and the Doha round. Others, meanwhile, launched themselves into FTAs. Before the EU's change of heart, it was the only leading power not to be engaged in FTAs in Asia. What do the new EU-Asia FTA negotiations mean - for the EU, for its Asian partners, and for the international trading system? I address this question in four parts. The first section summarises the state of EU-Asia trade relations. The next section puts the new negotiations in the context of overall EU FTA policy, and makes some comparisons with the US approach to FTAs. The third section summarises the ex ante state-of-play of FTAs in Asia, i.e. FTAs negotiated or underway in the region not involving the EU. The fourth and central section assesses prospects for EU negotiations with India, ASEAN and Korea. It also assesses the institutional framework for EU-China trade relations.
Keywords: 330